As simple but as complex as everyday cooking: Stanislavski's use of physical actions in the recreation of nature. Issue 2 (2nd July 2016) - Aquilina, Stefan
Abstract: This article considers Stanislavski's understanding of the "laws of nature" from the point of view provided by Henri Lefebvre's theories of everyday life. I will argue that Stanislavski's last years of work saw the application of his approach to physical actions as a means to create an organicity (or accordance) on stage between nature and acting processes. The term "physical actions" will be fine-tuned to "everyday physical actions" in order to contrast everyday life's seeming triviality with its potential to embody meaningful human relationships. The article will employ Stanislavski's rehearsal notes for a 1933 production of Artists and Admirers as a case-study and main source . These notes are not available in English translation and therefore reference to this production has rarely been made in the field of Stanislavski studies.